Engendering macroeconomic policy for gender equality in sub-Saharan Africa - Ibrahim A. Adekunle; Toluwani G. Kalejaiye; Ayomide O. Ogunade; Sina J. Ogede; Caleb O. Soyemi (African Governance and Development Institute (AGDI), 2020)
The social movement is inspiring meaningful conversation about the discriminatory practices' that Africa women have long faced in every aspect of their lives. However, despite considerable improvement in the gender balance discourse, the worst cases of gender imbalances are still recorded in sub-Sahara Africa (SSA). Macroeconomic volatility, both as a source and a reflection of underdevelopment, is a fundamental concern for women in SSA. This paper leans empirical credence to the role of macroeconomic policies (fiscal and monetary policies indices) for gender equality in SSA from 1993 through 2017. We gathered panel data on the indices of macroeconomic policies and gender inequality in all 48 SSA countries. We employed the dynamic panel system generalised method of moments estimation procedure (dynamic system GMM) to establish a baseline level relationship between the variables of interest. We adjusted for heterogeneity assumptions inherent in ordinary panel estimation and found a basis for the strict orthogonal relationship among the variables. Our results suggest fluctuations in macroeconomic policies as a lead factor for gender equality in SSA countries. Efforts should be tailored towards balanced macroeconomic policies that can guarantee sustainable gender equality approaches to collective prosperity.
Keywords: C33; E61; I18; J16; 330; Macroeconomic Policy; Gender Equality; Dynamic GMM; Sub-Sahara Africa